2018
DOI: 10.1103/physrevlett.121.247001
|View full text |Cite
|
Sign up to set email alerts
|

Light Bipolarons Stabilized by Peierls Electron-Phonon Coupling

Abstract: It is widely accepted that phonon-mediated high-temperature superconductivity is impossible at ambient pressure, because of the very large effective masses of polarons/bipolarons at strong electron-phonon coupling. Here we challenge this belief by showing that strongly bound yet very light bipolarons appear for strong Peierls/Su-Schrieffer-Heeger coupling. These bipolarons also exhibit many other unconventional properties, e.g. at strong coupling there are two low-energy bipolaron bands that are stable against… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 55 publications
4
67
0
Order By: Relevance
“…Understanding the physics of quasiparticles is important beyond cold atom settings in semiconducting [65] and superconducting devices [66]. Additionally, interactions among quasiparticles in liquid helium mixtures [67,68] and cuprates [69,70] are considered to be responsible for conventional and high-T c superconductivity [71][72][73][74][75][76][77]. Here we consider a Bose-Einstein condensate (BEC) with one or two impurities of either bosonic or fermionic nature immersed into it and track the emergent Bose polaron formation [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] with a PPS radiofrequency protocol analogous to the one used in the experiment of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the physics of quasiparticles is important beyond cold atom settings in semiconducting [65] and superconducting devices [66]. Additionally, interactions among quasiparticles in liquid helium mixtures [67,68] and cuprates [69,70] are considered to be responsible for conventional and high-T c superconductivity [71][72][73][74][75][76][77]. Here we consider a Bose-Einstein condensate (BEC) with one or two impurities of either bosonic or fermionic nature immersed into it and track the emergent Bose polaron formation [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] with a PPS radiofrequency protocol analogous to the one used in the experiment of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Lattice dimerization in one-dimension was initially described by the Su-Schrieffer-Heeger (SSH) model 1 , in which the atomic motion modulates the overlap integrals between neighboring atoms. Recently, SSH-like models have attracted further attention due to the fact that they can produce highly mobile polarons with light effective masses 9 , generate robust phonon-mediated pairing 10 , and even stabilize and control the location of a type-II Dirac point 11 . SSH interactions are also believed to be dominant mechanism for electron-phonon (e-ph) interactions in materials like the high-T c cuprates 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…These include a nearest neighbor repulsion for parallel spins, on-site pair terms (which will be suppressed by U ), and pair hopping of nearest-neighbor singlet pairs. Recent work has shown that this pair hopping interaction leads to strongly bound bipolarons with light effective masses that are stable against strong e-e interactions [30]. This suggests the possibility of e-p mediated SC in the presence of strong e-e interactions at finite carrier densities.…”
mentioning
confidence: 97%